Real time visualization of template directed colloidal self assembly - Zhao, Qin (2013)
Colloidal spheres play an important role as building blocks to fabricate basic photonic materials and lithographic masks, as they can self assemble into close packed 2D and 3D periodic arrays. In order to obtain more complex structures, patterned substrates have been used to direct the colloidal crystallization. However, the detailed mechanism of self-assembly onto a patterned substrate is not yet fully understood. Therefore, in situ visualization of colloidal self-assembly process on patterned substrate could be valuable. In this work, we investigated the size effect of the periodic patterns on dynamic colloidal self assembly during horizontal evaporation in a sessile drop. [3rd Award]